Attenuation of Piwil2 induced by hypoxic postconditioning prevents cerebral ischemic injury by inhibiting CREB2 promoter methylation. (6th July 2022) - Zhan, Lixuan; Chen, Meiyan; Pang, Taoyan; Li, Xinyu; Long, Long; Liang, Donghai; Peng, Linhui; Sun, Weiwen; Xu, En
Abstract: Epigenetic modification contributes to the pathogenesis of cerebral ischemia. Piwil2 belongs to the PIWI proteins subfamily and has a key role in the regulation of gene transcription through epigenetics. However, the roles of Piwil2 in cerebral ischemia have not been investigated. In this study, we aim to elucidate the roles and the underlying molecular mechanisms of Piwil2 in ischemic tolerance induced by hypoxic postconditioning (HPC) against transient global cerebral ischemia (tGCI). We found that the expression of Piwil2 in CA1 was downregulated by HPC after tGCI. Silencing Piwil2 with antisense oligodeoxynucleotide (AS‐ODN) in CA1 after tGCI decreased the expression of apoptosis‐related proteins and exerted neuroprotective effects. Opposite results were observed after overexpression of Piwil2 induced by administration of Piwil2‐carried lentivirus. Furthermore, we revealed differentially expressed Piwil2‐interacting piRNAs in CA1 between HPC and tGCI groups by RNA binding protein immunoprecipitation (RIP) assay. Moreover, downregulating Piwil2 induced by HPC or AS‐ODN after tGCI caused a marked reduction of DNA methyltransferase 3A (DNMT3A), which in turn abolished the tGCI‐induced increase in the DNA methylation of cyclic AMP response element‐binding 2 ( CREB2 ), thus increasing mRNA and protein of CREB2. Finally, downregulating Piwil2 restored dendritic complexity and length, prevented the loss of dentritic spines, thereby improving cognitive function after tGCI. These data firstly reveal that Piwil2 plays an important part in HPC‐mediated neuroprotection against cerebral ischemia through epigenetic regulation of CREB2. Abstract : Schematic depicting mechanism by which HPC protects neurons against tGCI in CA1 through Piwil2‐mediated epigenetics.